2014
DOI: 10.1302/0301-620x.96b4.32171
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomised trial comparing the use of absorbable and metallic screws in the fixation of distal tibiofibular syndesmosis injuries

Abstract: Our aim was to compare polylevolactic acid screws with titanium screws when used for fixation of the distal tibiofibular syndesmosis at mid-term follow-up. A total of 168 patients, with a mean age of 38.5 years (18 to 72) who were randomly allocated to receive either polylevolactic acid (n = 86) or metallic (n = 82) screws were included. The Baird scoring system was used to assess the overall satisfaction and functional recovery post-operatively. The demographic details and characteristics of the injury were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 31 publications
0
28
0
3
Order By: Relevance
“…Randomize kontrollü çalışmalar sonrasında biyo-emilebilir vidalarla 4,5 mm metal vidalar ve paslanmaz çelik ile titanyum vidalar arasında klinik açıdan bir fark saptanmamış-tır. [62][63][64] Transsindesmotik ve suprasindesmotik vida yerleşimleri arasında klinik ve radyolojik bir fark yoktur; ancak, bir kadavra çalışmasında, eklem hattının 1-3 cm prokismalinden uygulanan tespitin yük verme sırasında stabiliteyi sağladığı, fakat 5 cm proksimalinden uygulandığında stabiliteyi sağlamada…”
Section: Ameliyat Sırasında Değerlendirmeunclassified
“…Randomize kontrollü çalışmalar sonrasında biyo-emilebilir vidalarla 4,5 mm metal vidalar ve paslanmaz çelik ile titanyum vidalar arasında klinik açıdan bir fark saptanmamış-tır. [62][63][64] Transsindesmotik ve suprasindesmotik vida yerleşimleri arasında klinik ve radyolojik bir fark yoktur; ancak, bir kadavra çalışmasında, eklem hattının 1-3 cm prokismalinden uygulanan tespitin yük verme sırasında stabiliteyi sağladığı, fakat 5 cm proksimalinden uygulandığında stabiliteyi sağlamada…”
Section: Ameliyat Sırasında Değerlendirmeunclassified
“…112,113 The composition of the screw has not been shown to differ in biomechanical testing nor does it significantly influence the radiographic or clinical outcomes; this is true in regards to bioabsorbable screws [114][115][116] and titanium screws. 117 Bioabsorbable screws may offer slightly increased range of motion 118 and obviate subsequent hardware removal but have a higher incidence of foreign body reactions. 118 If choosing a stainless steel screw, fixation can be achieved with 3.5-or 4.5-mm screws.…”
Section: Screw Composition Size Number and Cortices Engagedmentioning
confidence: 99%
“…117 Bioabsorbable screws may offer slightly increased range of motion 118 and obviate subsequent hardware removal but have a higher incidence of foreign body reactions. 118 If choosing a stainless steel screw, fixation can be achieved with 3.5-or 4.5-mm screws. There is biomechanical evidence to suggest that the 4.5-mm screw provides more resistance to shear stress, 119 although other studies showed no biomechanical difference.…”
Section: Screw Composition Size Number and Cortices Engagedmentioning
confidence: 99%
“…After reading the titles and abstracts, 244 studies that were duplicates or did not meet the eligible criteria were excluded. After reading the full text, 102 reports were excluded, and 16 published RCTs (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), with a total of 1208 patients, were ultimately included in the meta-analysis. A flow diagram of the study screening procedure and the results are shown in Fig.…”
Section: Identification Of Eligible Studymentioning
confidence: 99%
“…The number of patients requiring reoperation was reported in 9 studies (11,(14)(15)(16)(17)(18)20,24,26) with 669 patients. The meta-analysis showed that the incidence of reoperation in the MS group was significantly greater than that in the AS group (RR 0.08, 95% CI 0.03 to 0.18, I 2 ¼ 77%, p < .01; Fig.…”
Section: Incidence Of Reoperationmentioning
confidence: 99%